2011
DOI: 10.1016/j.apmr.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Hypersensitivity in Women With Fibromyalgia: Implications for Well Being and Intervention

Abstract: Objective To document sensory sensitivities to nonnoxious sensory stimuli in daily life for participants with fibromyalgia (FM). Design Descriptive study of a convenience sample using a self-report survey of sensory processing. Setting Participants were recruited from the general community. The procedure took place in a research room at the University of Wisconsin-Madison. Participants Women with FM (n=27) were compared with women with rheumatoid arthritis (RA) (n=28) and healthy pain-free women (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 24 publications
4
74
2
2
Order By: Relevance
“…Instead, it may also involve cortical mechanisms affecting other sensory modalities, if the information conveyed by that sensory system is relevant for the injured body part, for instance, visual input predicting imminent contact of an object with that body part. Supporting this possibility, patients with chronic pain often report hypersensitivity to a broad range of stimuli including non-somatosensory stimuli [11,44].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it may also involve cortical mechanisms affecting other sensory modalities, if the information conveyed by that sensory system is relevant for the injured body part, for instance, visual input predicting imminent contact of an object with that body part. Supporting this possibility, patients with chronic pain often report hypersensitivity to a broad range of stimuli including non-somatosensory stimuli [11,44].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] While no clear consensus presently exists on the terminology, the hallmark of this type of pain appears to be generalized hypersensitivity to a variety of stimuli including mechanical, thermal, olfactory, auditory, and visual cues. [36][37][38][39] Unlike traditional central sensitization triggered by persistent nociceptive and/or neuropathic input, it is often impossible to pinpoint the cause of sensory hypersensitivity. It is thought to occur throughout the CNS and may involve additional mechanisms such as a decrease in descending inhibition and neuroplasticity in pain processing areas of the brain.…”
Section: Understanding Chronic Painmentioning
confidence: 99%
“…[1,35,37,41,[80][81][82][83] In addition, hyperalgesia and allodynia are often found in patients with neuropathic pain or sensory hypersensitivity, but less so with nociceptive pain.…”
Section: Evaluating the Types Of Pain Potentially Contributing To Thementioning
confidence: 99%
“…FM patients report increased sensitivity to diverse stimuli among them also nociceptive input, which via different mechanisms converge to hypersensitize the central nervous system and in many manners are similar to patients with post-traumatic stress disorder, depression and other affective conditions [19][20][21][22][23][24][25][26]. Among other characteristics FM patients tend to report enhanced olfactory acuity [27]. However, not many studies have objectively assessed the olfactory sensitivity in FM patients and one recently published study reported slightly reduced odor identification with no significant differences in smell threshold or discrimination [28].…”
Section: Introductionmentioning
confidence: 99%